Successful Management of Myasthenia Gravis Crisis with Septic Shock and Arrhythmia using Plasmapheresis: A Case Report - Viandini, Riska Yulinta; Arie Zainul Fatoni (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Myasthenia gravis (MG) is an autoimmune disorder that causes muscle weakness. In severe cases, it can lead to myasthenic crisis, a life-threatening condition characterized by respiratory failure. Sepsis, a systemic inflammatory response to infection, can further complicate MG and increase the risk of mortality. This case report describes the successful management of a patient with MG crisis complicated by septic shock and arrhythmia using plasmapheresis. Case presentation: A 52-year-old male with a history of MG presented with progressive dyspnea, decreased consciousness, and oxygen desaturation. He was diagnosed with MG crisis, septic shock, and arrhythmia. The patient was treated with plasmapheresis, antibiotics, and supportive care. Following plasmapheresis, the patient showed significant improvement in muscle strength, respiratory function, and hemodynamic stability. The arrhythmia resolved, and the patient was eventually weaned off mechanical ventilation. Conclusion: This case report highlights the potential benefits of plasmapheresis in managing MG crisis complicated by septic shock and arrhythmia. Plasmapheresis may be considered as a therapeutic option in such cases to improve patient outcomes.